Illness and Treatment in Theological and Normative Viewpoints - Nabilla Andasari Putri; Ulfi Nurhida Mahardika; Eka Intan Kusuma Wardhani; Marina Ayu Ningtyas; Tri Oktarina; Muthoifin; Qoree Butlam; Mohamed Akhiruddin Ibrahim; Muhammad Hamma’Adama Ahmad (Walidem Institute and Publishing, 2023)
The purpose of this study is to find out Islamic ethics in addressing illness and treatment. Methods used with literature search and literature selection. The theoretical framework of this study is that the Covid-19 pandemic has touched on every aspect of human life and raised many ethical questions. Several debates took place in various healthcare communities related to the coronavirus. In addition, religious communities also face various questions and challenges related to the Covid-19 pandemic regarding spiritual beliefs, ritual practices, and moral principles of the community. The results of the study show that every Muslim believes that every disease has its cure but man's job is to research and find a cure. Treatment is a healing effort recommended by the Prophet SAW, even if it is part of a form of tawakkal to Allah SWT, but treatment is prohibited by using drugs from unclean or made from objects forbidden by Islam. In times of emergency, Islam provides rukhsoh (leeway) for treatment with the haram with some emergency conditions that scholars have explained. Except for khomr, khomr still cannot be used as medicine, because in khomr emergency conditions are not met.